Trade and Trees: How Trade Agreements Can Motivate Conservation Instead of Depletion - Bård Harstad (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Free trade can often lead to resource depletion, such as deforestation in the tropics. This paper first presents a dynamic model whereby the South (S) depletes to export the extracted units (timber) or the produce (beef) from land available after depletion. Because of the damages, the North benefits from trade liberalization only if the remaining stock is, in any case, diminished. For that reason, S speeds up exploitation. The negative results are reversed if the parties can negotiate a contingent trade agreement, whereby the allocation of gains from trade, and thus the location on the Pareto frontier, is sensitive to the size of the remaining stock. In equilibrium, S conserves to maintain its favorable terms of trade, S conserves more than in autarky, and more when the gains from trade are large. The parties cannot commit to future policies, but they obtain the same outcome as if they could.
Keywords: F18; F13; F55; Q56; Q37; 330; exhaustible resources; deforestation; international trade; trade agreements; environmental conservation; conservation goods; renegotiation